The Teaching Design Methods Under Educational Psychology Based on Deep Learning and Artificial Intelligence - Wang, Zewen; Cai, Lin; Chen, Yahan; Li, Hongming; Jia, Hanze (Frontiers in Psychology, 2021)
This study is to evaluate the practical application value of the teaching method under the guidance of educational psychology and artificial intelligence (AI) design, taking the deep learning theory as the basis of teaching design. The research objects of this study involve all teachers, students, and students’ parents of Ningbo Middle School. The questionnaires are developed to survey the changes in students’ performance before and after the implementation of the teaching design and the satisfaction of all teachers, students, and parents to different teaching methods by comparing the two results and the satisfaction ratings. All objects in this study volunteer to participate in the questionnaire survey. The results suggest that: (1) the effective return rates of the questionnaires to teachers, students, and parents are 97%, 99%, and 95%, respectively before implementation; while those after implementation are 98%, 99%, and 99%, respectively. Comparison on two return results suggests that there was no significant difference statistically (P > 0.05). (2) Proportion of scoring results before and after implementation is given as follows: the proportions of levels A, B, C, and D are 35%, 40%, 15%, and 10% before implementation, respectively; while those after implementation are 47%, 36%, 12%, and 5%, respectively. After the implementation, the proportion of level A is obviously higher than that before the implementation, and the proportions of other levels decreased in contrast to those before the implementation, showing statistically obvious differences (P < 0.05). (3) The change in the performance of each subject after 1-year implementation is significantly higher than that before the implementation, and the change in the average performance of each subject shows an upward trend. In summary, (1) the comparison on the effective return rate of the satisfaction survey questionnaire proves the feasibility of its scoring results. (2) The comparison of the survey scoring results shows that people are more satisfied with the new educational design teaching method. (3) The comparison on change in the performance of each subject before and after the implementation indirectly reflects the drawbacks of partial subject education, indicating that the school should pay the same equal attention to every subject.